Disseminated fusariosis in a patient with bone marrow aplasia, - Danielle Ferreira Chagas; Lucia Martins Diniz; Elton Almeida Lucas; Paulo Sergio Emerich Nogueira (Sociedade Brasileira de Dermatologia, 2020)
Abstract Fusariosis is a superficial or systemic infection, which occurs mainly in immunocompromised hosts, especially in patients with hematological neoplasia; 70%-75% of the cases present cutaneous manifestations. The disseminated form is rare and difficult to diagnose; even with specific treatment, the evolution is usually fatal. Currently, it is considered an emerging disease; in some centers, it is the second most common cause of invasive mycosis, after aspergillosis. The authors describe a case of a female patient with idiopathic bone marrow aplasia and disseminated fusariosis, who initially appeared to benefit from voriconazole and amphotericin B; however, due to persistent neutropenia, her clinical condition deteriorated with fatal evolution.